The incidence of low venous oxygen saturation on admission to the intensive care unit: a multi-center observational study in The Netherlands - van Beest, Paul A (BioMed Central, 2008)
BACKGROUND: Low mixed or central venous saturation (S(c)vO(2)) can reveal global tissue hypoxia and therefore can predict poor prognosis in critically ill patients. Early goal directed therapy (EGDT), aiming at an ScvO(2 )≥ 70%, has been shown to be a valuable strategy in patients with sepsis or septic shock and is incorporated in the Surviving Sepsis Campaign guidelines. METHODS: In this prospective observational multi-center study, we determined central venous pressure (CVP), hematocrit, pH, lactate and ScvO(2 )or SvO(2 )in a heterogeneous group of critically ill patients early after admission to the intensive care units (ICUs) in three Dutch hospitals. RESULTS: Data of 340 acutely admitted critically ill patients were collected. The mean SvO(2 )value was > 65% and the mean ScvO(2 )value was > 70%. With mean CVP of 10.3 ± 5.5 mmHg, lactate plasma levels of 3.6 ± 3.6 and acute physiology, age and chronic health evaluation (APACHE II) scores of 21.5 ± 8.3, the in-hospital mortality of the total heterogeneous population was 32.0%. A subgroup of septic patients (n = 125) showed a CVP of 9.8 ± 5.4 mmHg, mean ScvO(2 )values of 74.0 ± 10.2%, where only 1% in this subgroup revealed a ScvO(2 )value < 50%, and lactate plasma levels of 2.7 ± 2.2 mmol/l with APACHE II scores 20.9 ± 7.3. Hospital mortality of this subgroup was 26%. CONCLUSION: The incidence of low ScvO(2 )values for acutely admitted critically ill patients is low in Dutch ICUs. This is especially true for patients with sepsis/septic shock.